Business growth strategy at pt. Pamelindo sakti perkasa - Darda Natanegara, Maula; Ghazali, Achmad (The Indonesian Journal of Business Administration, 2018)
Abstract. PT. Pamelindo Sakti Perkasa is an established contractor of electrical, civil and printing since 2016. For two years, they built a network to other company or people and management system in company to run the business because they believe good networking and system are key factor to success. To support this research, extracting primary and secondary data has been carried out and then continued by analyzing the internal and external environment of PT. Pamelindo Sakti Perkasa. To discover the whole situation regarding the business issue and formulate the business  growth strategy by using growth strategy, tows matrix, and diamond strategy. The result of this research are that PT. Pamelindo Sakti Perkasa market has not reach target to gain more revenues although South Sumatera is a big market. PT. Pamelindo Sakti Perkasa is planning to get more revenues in South Sumatera market by forming an intensive communication with their existing customers and new potential customers, join e-procurement, and maintain their suppliers to get sustainable advantages. Furthermore, market development strategy is the most suitable strategy to South Sumatera market. Keywords:  South Sumatera, Contractor Company , Projects.